Changes in Corticospinal and Spinal Excitability to the Biceps Brachii with a Neutral vs. Pronated Handgrip Position Differ between Arm Cycling and Tonic Elbow Flexion - Forman, Davis A.; Richards, Mark; Forman, Garrick N.; Holmes, Michael W. R.; Power, Kevin E. (Frontiers in Human Neuroscience, 2016)
The purpose of this study was to examine the influence of neutral and pronated handgrip positions on corticospinal excitability to the biceps brachii during arm cycling. Corticospinal and spinal excitability were assessed using motor evoked potentials (MEPs) elicited via transcranial magnetic stimulation (TMS) and cervicomedullary-evoked potentials (CMEPs) elicited via transmastoid electrical stimulation (TMES), respectively. Participants were seated upright in front on arm cycle ergometer. Responses were recorded from the biceps brachii at two different crank positions (6 and 12 o’clock positions relative to a clock face) while arm cycling with neutral and pronated handgrip positions. Responses were also elicited during tonic elbow flexion to compare/contrast the results to a non-rhythmic motor output. MEP and CMEP amplitudes were significantly larger at the 6 o’clock position while arm cycling with a neutral handgrip position compared to pronated (45.6 and 29.9%, respectively). There were no differences in MEP and CMEP amplitudes at the 12 o’clock position for either handgrip position. For the tonic contractions, MEPs were significantly larger with a neutral versus pronated handgrip position (32.6% greater) while there were no difference in CMEPs. Corticospinal excitability was higher with a neutral handgrip position for both arm cycling and tonic elbow flexion. While spinal excitability was also higher with a neutral handgrip position during arm cycling, no difference was observed during tonic elbow flexion. These findings suggest that not only is corticospinal excitability to the biceps brachii modulated at both the supraspinal and spinal level, but that it is influenced differently between rhythmic arm cycling and tonic elbow flexion.